Weighted gene coexpression network analysis identifies specific transcriptional modules and hub genes related to intramuscular fat traits in chicken breast muscle. Issue 8 (1st April 2019) - Li, Guoxi; Zhao, Yinli; Li, Yuanfang; Chen, Yi; Jin, Wenjiao; Sun, Guirong; Han, Ruili; Tian, Yadong; Li, Hong; Kang, Xiangtao
Abstract: Intramuscular fat (IMF) traits are important factors that influence meat quality. However, the molecular regulatory mechanisms that underlie this trait in chickens are still poorly understood at the gene coexpression level. Here, we performed a weighted gene coexpression network analysis between IMF traits and transcriptome profile in breast muscle in the Chinese domestic Gushi chicken breed at 6, 14, 22, and 30 weeks. A total of 26 coexpressed gene modules were identified. Six modules, which included the dark gray, purple, cyan, pink, light cyan, and blue modules, showed a significant positive correlation ( P  < 0.05) with IMF traits. The strongest correlation was observed between the dark gray module and IMF content ( r  = 0.85; P  = 4e‐04) and between the blue module and different fatty acid content ( r  = 0.87~0.91; P  = 5e‐05~2e‐04). Enrichment analysis showed that the enrichment of biological processes, such as fatty acid metabolic process, fat cell differentiation, acylglycerol metabolic process, and glycerolipid metabolism were significantly different in the six modules. In addition, the 32, 24, 4, 7, 6, and 25 hub genes were identified from the blue, pink, light cyan, cyan, dark gray, and purple modules, respectively. These hub genes are involved in multiple links to fatty acid metabolism, phospholipid metabolism, cholesterol metabolism, diverse cellular behaviors, and cell events. These results provide novel insights into the molecular regulatory mechanisms for IMF‐related traits in chicken and may also help to uncover the formation mechanism for excellent meat quality traits in local breeds of Chinese chicken. Abstract : We, for the first time, performed a weighted gene coexpression network analysis between intramuscular fat (IMF) traits and genes in chicken. A total of 26 coexpressed gene modules were identified, six of them showed a significant positive correlation with IMF traits. Meanwhile, 98 hub genes were identified from six modules of interest.